Pengaksesan materi pembelajaran dalam dua sistem e-learning yang berbeda : Studi kasus Sinau dan Papirus - ADI, Veronika Julia Satia Nimpuno ([Yogyakarta] : Universitas Gadjah Mada, 2009)
The development of the Internet technology is very fasr today, and alsothe E-learning development. The need of E-learning is designed with the E-learning application based on Web. The problems are how the E-learning systems can be interaction with the another systems, which the data structure and application are different. The difficulties are how to access those systems with it depends on the learning materialss. So it needs the program to interaction the systems. This research is to solve the problem for accessing inter the E-learning systems. The solving problems is how to access the inter E-learning, with adopting the Web Service concept. The Web Service is designed and used the XML format, and it uses to build the publication in XML fomat. Reading that description, the access system can be used to build the own application without knowing the other access application. And by using the Web Service, the accessing the application can be done. Key Words : E-Learning, Web Services, XML.